Rational Solutions for the (2+1)-Dimensional Modified KdV-CBS Equation - Yan Li; Temuer Chaolu; Yuexing Bai (Advances in Mathematical Physics)
In this paper, with the help of symbolic computation, three types of rational solutions for the (2+1)-dimensional modified KdV-Calogero-Bogoyavlenkskii-Schiff equation are derived. By means of the truncated Painlevé expansion, we show that the (2+1)-dimensional modified KdV-Calogero-Bogoyavlenkskii-Schiff equation can be written as a trilinear-linear equation, from which we get explicit representation for rational solutions of the (2+1)-dimensional modified KdV-Calogero-Bogoyavlenkskii-Schiff equation.